An Economic Model for Creating a Network Enterprise Architecture - A. А. Bryzgalov; Yu. F. Telnov (Статистика и экономика, 2022)
The purpose of the study is to develop an economic justification model for creating a value chain for various types of digital platforms and technological methods of production of a network enterprise. As a basis for creating an economic justification model, it is proposed to use the method of functional and cost assessment of the architecture of a network enterprise, which determines the economic costs and risks of forming value chains that are associated with the production and provision of services of the enterprise.The novelty of the research lies in the fact that the economic justification for creating the architecture of a network enterprise should be carried out taking into account the dynamically changing needs of the customer and the state of the business ecosystem of the enterprise in the process of its functioning.The research methods are heuristic in nature, aimed at finding such a set of economic factors that will lead to the formation of an economically sound construction of the value chain. In order to obtain an economic model for creating the architecture of a network enterprise, a method of functional and cost estimation in the process of dynamic changes in the value chain is proposed.Results. This article presents an economic model for evaluating the architecture of a network enterprise, in which each element of the model is an economic aspect of the formation of value chains for a network enterprise. The analysis of economic aspects made it possible to determine in more detail the costs, including the costs of eliminating risks.In addition to the economic justification model for creating a value chain, the paper identifies requirements for the architecture of a network enterprise and the possible composition of the roles of participants as well as the definition of network effects for different roles. In order to display the relationship between the type of digital platform and the technological method of production, when conducting a cost assessment of the architecture of a network enterprise, all calculated estimates are introduced into the cost and risk assessment matrix. As a result, depending on the chosen type of digital platform and technological method of production, the search for minimum costs and risks for a specific value chain is carried out.Conclusion. The economic model of the cost assessment of the architecture of a network enterprise, made on the basis of the use of the method of functional-value cost analysis and risk analysis, will allow for resource justification of the configuration of value chains with an optimal distribution of roles of network enterprise participants.